Comparing the effectiveness of education based on positive psychology with education based on cognitive-behavioral method on the resilience of students of gifted schools in Tehran - adel khaleghy samarin; Hasan Ahadi; Ali Asghar Asgharnejad Farid; GholamReza Sarami Foroushani; Mahdiyeh Rahmaniyan (مطالعات روانشناسی تربیتی)
The purpose of the present study was to compare the effectiveness of education based on positive psychology with education based on cognitive-behavioral method on the resilience of students of gifted schools. The research method was a pre-test-post-test experiment with a control group. The statistical population included all the students of gifted schools, studying in the first secondary level in the academic year 2016-2017 (about 12000 people), from which a sample of 45 people was selected using cluster random sampling method. and randomly placed in two experimental groups and one control group. Connor and Davidson (2003) resilience questionnaire was used to collect data. The experimental groups were trained for 14 sessions of 90 minutes based on positive psychology (Seligman and Rashid, 2006) and cognitive-behavioral method (Beck et all, 1988), but the control group did not receive any intervention. The findings showed that the difference between the experimental and control groups is significant in both approaches, and education based on positive psychology and cognitive-behavioral education had the greatest impact on the resilience of gifted school students, respectively (P=0.001). ). Based on the findings, it can be concluded that people can achieve more resilience by learning techniques based on positive psychology and cognitive-behavioral methods, but education based on positive psychology is more successful than cognitive-behavioral methods. have.